Production Cost Treatment and Contribution Margin in Mamasa Weaving - Todingbua, Manuel August (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Kristen Indonesia Paulus, 2023)
Production costs are one of the determining variables in determining the selling price of a product to be produced. This research, which was conducted on the Mamasa weaving business, aims to find out how to determine the production costs of the Mamasa weaving business. Mamasa weaving is one of Mamasa's special crafts that still survives to this day. Production cost analysis method and contribution margin analysis. The types of data used in this study are quantitative and qualitative with the methods used in collecting data, namely observation and interviews. The calculation of production costs carried out by the craftsmen when compared with the calculation of production costs with the production cost analysis method and the contribution margin analysis shows a difference, this occurs because the calculations made by the craftsmen are only the raw material costs which are recognized as expenses while in the analysis method production costs the calculated expenses are the cost of raw materials, labor costs and overhead costs. Comparison of calculations made by craftsmen with production cost analysis methods have differences, this happens because in the application of production cost analysis methods there are additional production cost calculations, namely labor costs, overhead costs including equipment depreciation costs.